دراسة تأثير بعض المبيدات الفطرية في مكافحة مرض عين الطاووس في الزيتون المتسبب عن الفطر Spilocaeaoleagina (Cast) Hugh (Latakia University Journal -Biological Sciences Series, 2016)
To know the effect of some fungicides on peacock eye disease has beentested five fungicides from different chemical groups, using concentrations advisable to field application,on the 45 year old olive trees in the Baksa village Lattakia . The results showed an increase in incidence of the control of 22.4 to 45.5 % after 45 days, versus low incidence rates in the fungicides tested treatments . The best two fungicides were thiophanate –methyl with infection decreasing from 19.2 to 10.3% and chlorothalonil from 24.3% to 16.5% . The severity also decreased in the treatment of the fungicide thiophanate –methyl from 9.7 to 4.1 % and chlorothalonil from 13.7 to 8.9 % while the severity of the infection of the control increased from 10.5 to 25.6 % .In order to efficiency the fungicide thiophanate – methyl was more effective reducing the infection severity compared with the control with 82.8 %, followed by chlorothalonil , kresoxsim methyl , and mancozeb with 73.3 , 72.0 , 71.9% respectively whereas the fungicide copper oxychloride was the least effective with 68.1%.تم اختبار خمسة مبيدات من مجموعات كيميائية مختلفة باستعمالها بالتركيز المنصوح به حقلياً على أشجار زيتون بعمر أكثر من 45 سنة في قرية بكسا من محافظة اللاذقية لمعرفة تأثيرها في مرض عين الطاووس. أظهرت النتائج تزايد نسبة الإصابة للشاهد من 22.4إلى45.5 %بعد 45 يوماً، في حين انخفضت نسبالإصابة في معاملات المبيدات المختبرة. فكان أفضلها المبيدان ميثيل ثيوفانات؛ إذْ انخفضت نسبة الإصابة من 19.2إلى%10.3 والمبيد كلوروثالونيل من 24.3إلى16.5 %، كما انخفضت شدة الإصابة في معاملة المبيد ميثيل ثيوفانات من 9.7إلى%4.1والمبيد كلوروثالونيل من 13.7إلى%8.9،في حين ارتفعت شدة الإصابة للشاهد من 10.5إلى %25.6.بالنسبة إلى الفاعلية وجد أن المبيد ميثيل ثيوفانات أكثر المبيدات تأثيراً؛ إذْ أسهم في خفض شدة الإصابةمقارنة مع الشاهد، وكانت الفاعلية 82.8 % ، تلاه المبيداتكلوروثالونيلوكريزوكسيم الميثيل ومانكوزيب بفاعلية 73.3 ،72.0 ، 71.9% على التوالي، وكان المبيد أوكسي كلور النحاس الأقل فاعلية؛ إذْ لم تتجاوز 68.1%.